Isolation and Selection of Biosurfactan Producing Bacteria from the Pond in the Gathering Station EOR Plant PT. Bumi Siak Pusako Pertamina Hulu Riau Province - Sardion Simatupang; M.Hasbi M.Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The water in the pond at PT Bumi Siak Pusako-Pertamina Upstream Eor Plant Gathering Station is polluted by oil. The presence of oil in pond water triggers gene mutations in bacteria so that the bacteria can produce biosurfactants to degrade oil. The aim of this study was to obtain a biosurfactant-producing bacterial isolate and was carried out in January - February 2019. Bacterial isolation was started by taking 5 ml of pool water samples and mixed with 40 ml of Bacterial Fertilizing media namely Brain Heart Infusion (BHI) and then incubated for 1 x 24 hours . Then the bacteria are grown using Mac conkey media. Pure bacteria are biochemically tested and emulsified. Morphological and biochemical characteristics show that 2 species of bacteria, namely Provindensia sp and Citrobacter sp. Emulsification index results show that all bacteria obtained have the potential to produce biosurfactants.Keywords: Providensia sp, Citrobacter sp